Pengaruh Kepemimpinan Transformasional, Motivasi Kerja dan Budaya Organisasi Terhadap Komitmen Organisasional Pada PT. Kembang Jawa Permai - Sawalinda, Refi; Mahyudi Saputra, Beny; Sri Hardiningrum, Iing (FEB Universitas Maritim Semarang, 2025)
This study aims to examine the influence of transformational leadership, work motivation, and organizational culture on organizational commitment at PT Kembang Jawa Permai. The research employs a quantitative approach with an associative causal design, using a survey method and data collected through a questionnaire distributed to all 46 employees as respondents. The sampling technique used is saturated sampling, considering the small population size. Data analysis was performed using multiple linear regression analysis with validity, reliability, and classical assumption tests (normality, multicollinearity, heteroscedasticity, and linearity) conducted beforehand to ensure model accuracy. The results indicate that transformational leadership, work motivation, and organizational culture each have a positive and significant effect on organizational commitment, both partially and simultaneously. Among the three variables, organizational culture shows the most dominant influence, indicating that strong organizational values and teamwork orientation play a key role in strengthening employee commitment. The coefficient of determination (R²) of 0.848 implies that 84.8% of the variation in organizational commitment can be explained by the three independent variables. This study contributes to human resource management theory and provides practical insights for organizations to enhance employee commitment through effective leadership, motivation, and cultural reinforcement.